Efficient phase‐field modelling of fatigue crack propagation. Issue 1 (18th November 2019) - Seiler, Martha; Linse, Thomas; Hantschke, Peter; Kästner, Markus
Abstract: Fatigue loads come along with high numbers of load cycles which makes the simulation of fatigue fracture computationally very demanding. We present a numerically efficient method which avoids resolving the loading path and instead requires only one increment per load cycle at most. We combine the phase‐field method for fracture with a classic fatigue concept. A local lifetime variable is obtained, which we use to modify the material resistance incrementally in order to consider the progressive weakening of the material. Focussing on ductile material behaviour, we make use of an elasto‐plastic revaluation technique instead of a full plastic material model. The model allows to describe fatigue crack initiation as well as propagation and reproduces Paris behaviour.